A Paradigm Shift in Human Resources through the Integration of ChatGPT in Talent Management and Beyond - Limna, Pongsakorn; Kraiwanit, Tanpat; Yuenyong, Nithima (Journal of Multidisciplinary in Social Sciences, 2026)
This study examines the integration of generative artificial intelligence (AI), particularly ChatGPT, in human resource (HR) management and its transformative potential in talent management practices. A qualitative research design was adopted, involving in-depth interviews with 15 HR professionals, including frontline staff, managers, and key stakeholders from HR organizations in Krabi, Thailand. The data were analyzed using content analysis supported by NVivo software to identify key themes related to the application of ChatGPT in HR functions. The findings indicate that ChatGPT can streamline recruitment and candidate screening processes, enhance employee onboarding and training, support employee engagement and well-being initiatives, facilitate data-driven decision-making, promote diversity and inclusion, and improve HR self-service operations. To strengthen practical implementation, the study recommends a phased adoption strategy, beginning with administrative tasks and gradually expanding to decision-support functions. Organizations are also advised to establish clear ethical guidelines, continuously monitor AI-generated outputs, and integrate AI tools with human expertise to ensure an appropriate balance between automation and professional judgment. The study offers practical implications for HR practitioners, including the development of AI competency training, refinement of AI-assisted decision-making processes, and the promotion of transparency in AI-supported recruitment and performance evaluation systems. Overall, the findings provide a strategic framework for leveraging ChatGPT to enhance efficiency, fairness, and innovation in HR management. As AI technologies continue to evolve, responsible and ethical implementation will be essential to fostering a more effective and employee-centered HR environment.